PEMANFAATAN KUNYIT (Curcuma domestica Val) DAN JERUK NIPIS (Citrus aurantifolia Swingle) DALAM PEMBUATAN ABON IKAN LEMURU - Djoko Poernomo; Agoes Mardiono Jacoeb; Uut Tri Utami; Roni Nugraha (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2010)
The research objectives were determine the concentration of lime and soaking time that could reduce the smell of sardine, the concentration of curcumin that could prevent the oxidation of fish, and the effect of curcumin on chemical and microbiology characteristic of sardine abon during 30 days storage. Sardine was soaked in lime solution with concentration from 5 to 20% (v/v) for 10, 20, and 30 minutes. After the best concentration of lime was found, the experiment was continued to determine the optimum concentration of curcumin in maintained he chemical and microbiology characteristic of sardine abon by adding the fish with curcumin from 1% to 5% (w/w). The abon was stored for 30 days andevery 10 days the sensory test, proximate analysis, analysis of water activity (aw), TPC and TBA were carried out. Sensory test showed that the addition of lime until 15% could increase the result, however, the sensory test result depleted when 20% of lime was used. The period of immersion also gave positive correlation with sensory test. The preliminary experiment also showed that the addition of curcumin increased the value of sensory test with 1 and 2% of curcumin gave better result compared with 3, 4 and 5% curcumin. During 30 days storage period, the value of sensory parameters and proximate properties were decrease, meanwhile, the water activity, TPC and TBA were rised. In conclusion, up to 30-day storage period, teh quality of fish abon was decrease,d but still could be accepted by the panelists. Immersion of fish abon on 15% of lime for 30 minutes and addition of 2% curcumin gave better quality of fish abon compared with others treatmen with value of water content 10.71%, ash4.16%, fat 26.82%, protein 30.51%, carbohydrate 27.80%, aw 0.51, TPC 2.45 colonies/ gram, and TBA 1.76mg/kg. The addition of curcumin fish abon did not significantly influence the appearance, water content, ash, fat, and carbohydrates, however the color, aroma, texture, flavor, protein content, water activity (aw), value TBA, and TPC significantly influenced.Keywords: curcumin, fish abon, lime, sencory parameters